Effect of parachlorophenylalanine, a specific 5-HT depleter on fluoxetine and d-fenfluramine induced penile erections in rats - Kanhaiah, More; M Thorat, Vandana; R Shinde, Anjali; G Gursale, Santosh (International Journal of Medical Research and Review, 2015)
Objective: To determine whether fluoxetine (FLU) induces penile erection (PE) in rats either indirectly via its 5-HT neuronal reuptake inhibiting activity or directly by stimulating the 5-HT2c receptors in the brain. Method: The effect of pre-treatment with para-Chlorophenylalanine (PCPA) on fluoxetine and d-fenfluramine (d-FEN) induced PEs (Penile erections) was studied in albino rats. Results: FLU (10mg/kg) and d-FEN (2.5mg/kg) treated groups exhibited a significant increase in number of PEs as compared to their respective control (DW treated) groups. Pre-treatment with PCPA (100mg/kg/day) had no significant effect on the PEs induced by FLU (10mg/kg) but did significantly decrease the PEs induced by d-FEN (2.5 mg/kg). Conclusion: Our results indicate that pre-treatment with selective 5-HT depleter PCPA (100mg/kg/day) significantly decreased PEs induced by d-FEN (2.5mg/kg) but had no significant effect on the number of PEs induced by FLU (10 mg/kg). This indicates that the PE inducing effect of FLU is probably due to the stimulation of 5HT2C receptors.